Huntington’s disease: Neural dysfunction linked to inositol polyphosphate multikinase - Ahmed, Ishrat (Proc Natl Acad Sci U S A, 2015)
Huntington’s disease (HD) is a progressive neurodegenerative disease caused by a glutamine repeat expansion in mutant huntingtin (mHtt). Despite the known genetic cause of HD, the pathophysiology of this disease remains to be elucidated. Inositol polyphosphate multikinase (IPMK) is an enzyme that displays soluble inositol phosphate kinase activity, lipid kinase activity, and various noncatalytic interactions. We report a severe loss of IPMK in the striatum of HD patients and in several cellular and animal models of the disease. This depletion reflects mHtt-induced impairment of COUP-TF-interacting protein 2 (Ctip2), a striatal-enriched transcription factor for IPMK, as well as alterations in IPMK protein stability. IPMK overexpression reverses the metabolic activity deficit in a cell model of HD. IPMK depletion appears to mediate neural dysfunction, because intrastriatal delivery of IPMK abates the progression of motor abnormalities and rescues striatal pathology in transgenic murine models of HD.